9: Assessing Healthcare Needs and Research Barriers for Community Focused Interdisciplinary Health Research Capacity Building Using a Microresearch Model in East Africa. Issue 6 (1st June 2014) - Bortolussi, R; MacDonald, N; Moraca, S; Grant, E
Abstract: BACKGROUND: With barely 3% of health care workers (HCW) and over 25% of the global health burden, Sub-Sahara African nations saw an urgent need to build capacity in community focused research in 2008 (WHO Bamako 'Call for Action'). Borrowing from principles of microfinance, MicroResearch (MR) provides training, coaching and small grants for community focused interdisciplinary research (CFIR) and knowledge translation. OBJECTIVES: To assess if MicroResearch addresses the local need for CFIR in East Africa (EA). DESIGN/METHODS: We used targeted on-line surveys to assess health challenges and barriers for EA HCW researchers. In phase 1, questionnaires to assess health care challenges were sent to senior researchers (deans, department heads) and junior HCW engaged in CFIR. In phase 2, we assessed an on-line focus group of community researchers from five academic sites in EA using qualitative analyse of responses to prompted questions. RESULTS: In phase 1, 68 questionnaires were distributed, and 40 (59%) responded, 17 from senior and 23 junior HCW researchers. The two groups were pooled since response differences were <3% to most questions. Access to healthcare (36%), social determinants (33%) and health service infrastructure (21%) were the most common healthcare needs identified. Lack of research skills (design, analytic methods, training programs), capacity (coaching, mentoring), and funding were identified, as common research capacity needs. Both groups recommended research funding be directed to community (33%), health system (25%) or epidemiologic research. In phase 2, a focus group of 10 multidisciplinary participants (five female, five male) was formed. There were 16 valid comments with 21 points raised for saturation to be reached. Thematic content analysis and summaries were made at stages of the analysis. The four main thematic areas identified as barriers to health research, listed in order of frequency, were; Knowledge, Finance, Mentorship/Coaching, and Ethical Regulation/clearance, Incentives. CONCLUSIONS: Healthcare needs and barriers to research for CFIR in EA were identified in surveys of senior and junior East African HCW. Strategies, like MR, are addressing these capacity building issues.